2023
DOI: 10.3390/molecules28134900
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Lycopene and Curcumin Synergistically Alleviates Testosterone-Propionate-Induced Benign Prostatic Hyperplasia in Sprague Dawley Rats via Modulating Inflammation and Proliferation

Abstract: Background: Benign prostatic hyperplasia (BPH) is a progressive urological disease occurring in middle-aged and elderly men, which can be characterized by the non-malignant overgrowth of stromal and epithelial cells in the transition zone of the prostate. Previous studies have demonstrated that lycopene can inhibit proliferation, while curcumin can strongly inhibit inflammation. This study aims to determine the inhibitory effect of the combination of lycopene and curcumin on BPH. Method: To induce BPH models i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Studies have shown that BPH manifestation is associated with elevated testosterone and inflammation [ 14 , 42 ]. A positive correlation between elevated serum E 2 levels and the development of BPH has also been reported [ 43 ]. Also, prostatic inflammation contributes greatly to elevated serum levels of PSA [ 14 ].…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that BPH manifestation is associated with elevated testosterone and inflammation [ 14 , 42 ]. A positive correlation between elevated serum E 2 levels and the development of BPH has also been reported [ 43 ]. Also, prostatic inflammation contributes greatly to elevated serum levels of PSA [ 14 ].…”
Section: Discussionmentioning
confidence: 97%